Comparacion de sistemas de captura de afidos (Homoptera, Aphidinea) en citricos - hermoso, A.=700 1 Perez, A.; Carbonell, E.A.; Real, V.
(Es, En)
ilus., 9 ref.
Keywords: APHIDOIDEA; CITRUS; TRAMPAS; ESPAÑA; AFIDOS; CITRICOS